POLITICAL CORRUPTION AS EROSION OF THE RIGHT AND THE PRAYER - Paneva Parleeva, Biljana (Journal of process management and new technologies, 2018)
In the last 20 years despite the discovery of the ever-increasing factors of political corruption, as well as the "everyday seemingly" tackling of political corruption and the preventive actions of state institutions, our country cannot boast some significant changes in this field: old problems have not yet been resolved, and existing problems prevail daily. Many political actors in the country, that is, those politicians who have "welled up" with oppressive political incursions in order to grab their own benefit or for the benefit of the political party they represent, would secretly say that it is good that there is corruption, "Lubricates" the business in conditions when it cannot run in a fast, regular way. The scientific paper analyzes the negative impact of this phenomenon in our country, as well as its negative consequences on the rule of law, the destruction of the human individual and morality, the destruction of the market economy, free competition, and so on.